The potential beneficial effects of sildenafil and diosmin in experimentally-induced gastric ulcer in rats - Alaa E. El-Sisi; Samia S. Sokar; Sally E. Abu-Risha; Doaa Y. Khira (Heliyon, 2020)
Objectives: research in the treatment of gastric ulcer has involved the investigation of protective drugs. These drugs may be used as adjacent therapy with the traditional pharmacologic treatment of peptic ulcer. The present study is designed to investigate the gastro protective effects of diosmin (DIO), sildenafil (SILD) and their combinations with ranitidine (RANT) against indomethacin (INDO)-induced gastric ulcer in rats. Additionally, the potential mechanisms of their effect are addressed. Methods: DIO (100 mg/kg) and SILD (10 mg/kg) were administered by oral route for seven days prior to ulcer induction. Moreover, other rats were treated with RANT (50 mg/kg) not only to compare efficiency of the medications but also, to help clarify potential mechanisms of their effect. Following, after 24 h of fasting, INDO (100 mg/kg) was administered for induction of gastric ulcer. Furthermore, rats in each group were sacrificed 4 h later. Biochemical analysis of DIO, SILD, RANT and their combinations pre-treated host tissues demonstrated reduction in tumor necrosis factor (TNF)-α and malondialdehyde (MDA) contents and concomitant increase in gastric pH, nitric oxide (NO) and reduced glutathione (GSH) contents. Result: It is observed, that SILD and DIO pre-treatment showed non-significant effect on gastric juice PH. However, their combinations with RANT is superior to using RANT alone. In addition, the results revealed, that combinations of (RANT and SILD) and (RANT and DIO) showed the highest increase in gastric tissue NO levels. But, these two combinations achieved the lowest MDA levels relative to the control (INDO) group. Despite, all groups displayed non-significant effect on reduced GSH content, (RANT and SILD) group increased GSH concentration by 39.75% relative to INDO group. In addition, DIO, RANT and (RANT and DIO) pre-treatment have anti-apoptotic activity on gastric mucosa. On the other hand, SILD did not affect caspase-3 immunostaining. These results are confirmed by histopathological findings. Conclusion: The work outcomes provide a new gastro protective agents in clinical gastropathy. So, this study not only provides an efficient way for peptic ulcer protection, but also it may be considered for future studies in ulcer healing and gastric cancer.